Coton Park, Rugby, Warwickshire : a middle Iron Age settlement with copper alloy casting - Chapman, Andy, 1951- (Archaeopress Archaeology, 2020)
A total area of 3.1ha, taking in much of a settlement largely of the earlier Middle Iron Age, was excavated in 1998 in advance of development. The Iron Age settlement comprised several groups of roundhouse ring ditches and associated small enclosures forming an open settlement set alongside a linear boundary ditch. This title considers the physical, social, and economic structure of the settlement.